2021
DOI: 10.1186/s11689-021-09360-7
|View full text |Cite
|
Sign up to set email alerts
|

Modeling familial predictors of proband outcomes in neurogenetic disorders: initial application in XYY syndrome

Abstract: Background Disorders of gene dosage can significantly increase risk for psychopathology, but outcomes vary greatly amongst carriers of any given chromosomal aneuploidy or sub-chromosomal copy number variation (CNV). One potential path to advance precision medicine for neurogenetic disorders is modeling penetrance in probands relative to observed phenotypes in their non-carrier relatives. Here, we seek to advance this general analytic framework by developing new methods in application to XYY syn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 32 publications
(45 reference statements)
0
8
0
Order By: Relevance
“…Whereas the sex chromosome trisomies (XXY, XYY and XXX syndromes) are all associated with a ~ 10 point reduction in full scale IQ on average (slightly larger decrements for verbal as compared to performance IQ), reported mean IQs are typically lower in XXYY syndrome [8,19,20,30,31]. However, there is marked interindividual variability in IQ within all SCA groups [32][33][34], and it remains unclear how this is related to the co-occurring interindividual variation that has been described for psychopathology. Work in non-SCA groups suggests there can be complex correlations between clinical variation in IQ and psychopathology [35][36][37][38][39][40][41][42][43][44][45], but the few studies addressing this question in SCA have focused on individual domains of psychopathology [8], prompting the clinically important question of whether some psychiatric features are more strongly coupled to cognitive ability than others in SCA.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the sex chromosome trisomies (XXY, XYY and XXX syndromes) are all associated with a ~ 10 point reduction in full scale IQ on average (slightly larger decrements for verbal as compared to performance IQ), reported mean IQs are typically lower in XXYY syndrome [8,19,20,30,31]. However, there is marked interindividual variability in IQ within all SCA groups [32][33][34], and it remains unclear how this is related to the co-occurring interindividual variation that has been described for psychopathology. Work in non-SCA groups suggests there can be complex correlations between clinical variation in IQ and psychopathology [35][36][37][38][39][40][41][42][43][44][45], but the few studies addressing this question in SCA have focused on individual domains of psychopathology [8], prompting the clinically important question of whether some psychiatric features are more strongly coupled to cognitive ability than others in SCA.…”
Section: Introductionmentioning
confidence: 99%
“…Future work should also aim to distinguish possible biological and familial predictors of phenotypic variability. For example, multiple linear regression models have shown that individuals with XYY and their family members are correlated on certain traits, such as IQ, vocabulary, and social awareness (Wilson et al 2021 ). Efforts to understand the clinical utility of these models in the genetic counseling setting will be useful in providing anticipatory guidance for families.…”
Section: Areas For Future Researchmentioning
confidence: 99%
“…All participants were free from MRI contraindications. We estimated power based on previous work demonstrating a correlation between parent and child IQ in XYY syndrome (r=0.63)[34]. Using a more conservative r value of 0.50, the estimated power to detect an association between parent and child IQ for a cohort of 53 families is 0.98.…”
Section: Methodsmentioning
confidence: 99%